Giant juvenile fibroadenoma mammae case report - Abidin, Zainal (Science Midwifery, 2024)
Mammae fibroadenoma (FAM) is a benign breast tumor with a mass consisting of epithelial tissue and stroma located under the skin of the breast. Fibroadenomas are mostly experienced in young women aged 10-18 years. The cause is not yet known for sure, but it is suspected that an increase in hormones occurs at a young age. FAM which is rapidly enlarged in size with a tumor diameter of more than 5 cm and weighs more than 500 grams is called Giant Juvenile Fibroadenoma. Characteristics of Giant Juvenile Fibroadenoma Mammae, although it is a benign tumor, can compress the surrounding tissue and change the structure of the lobules due to its increase in size and vascularization, and is at risk of leading to malignancy indicators. The case report reported one case in an 11-year-old girl with a major complaint of a lump in the left breast, rapidly enlarging over the past 6 months before being admitted to hospital. Preoperative cytology using Fine Needle Aspiration (FNA) showed the presence of Giant Juvenile Fibroadenoma (GJF) Mammae. The patient was given wide excision surgery with a surgical margin of 1 cm followed by a mastectomy procedure. A tumor measuring 7 x 7 cm was obtained with hypervascularization. Histopathological reports show benign juvenile giant fibroadenoma mammaries with negative margins. At follow-up up to 6 months, there were no signs of recurrence on physical examination and ultrasonography.